APPLICATION OF STEM-BASED WORKSHEETS TO INCREASE INTEREST AND LEARNING OUTCOMES OF 5TH GRADE STUDENTS IN CHANGING STATES OF MATTER - Nadhifah, Nisa; Supriadi, Bambang; Handayani, Rif'ati Dina; Mariya, Mariya (JPSD (Jurnal Pendidikan Sekolah Dasar), 2022)
AbstractThis research aims to increase the interest and learning outcomes of 5th grade students at SDN Triwung Lor 2 by applying STEM-Based student worksheets on the material of changing state of matter. This research is a Classroom Action Research (CAR) conducted on 22 students of 5th grade at SDN Triwung Lor 2 Probolinggo City, consisting of 10 male and 12 female students. The data were collected through observation sheets, questionnaire sheets, pre-tests, and post-tests. The increase in student’s interest and learning outcomes was calculated by N-gain. The results showed that STEM-based worksheets could increase student’s interest and learning outcomes with the N-gain score on learning interest of cycle I and cycle II included with low criteria. While the learning outcomes experienced an insignificant increase because the learning outcomes in cycle I were included in the moderate criteria and cycle II were included in the low criteria. This research concludes that the application of STEM-based worksheets can increase student’s interest and learning outcomes.Keywords: Student Worksheets; Learning Interest; Learning Outcomes